Clues to school organization for the development of students´ skills in 21st century - Villadiego-Sánchez, Levis (2022)
This article develops the conceptual elements that support the relevant components of school organization to develop competencies in students in response to the demands of the information,knowledge and learning society. Different strategies are proposed that operates the bases according to the new approach of the social agreement CTS (Science, Technology and Society) to getover the old positivist model and set it on an approach that deals not only with the interest of science, but also the needs and the problems of social context, this situation enlarge its relevance, extension and applicability. It develops initially the need to prioritize over the design, implementation and the review of the public policies which constitute the guide or orientation of education, later the need to restructure the curricular designs to answer to the interest, needs that society considers relevant giving the importance to the implementation of strategies that reinforce learning on net and the competences to learn how to learn in an highly changing environment. Finally, it analyzes the implications of the teacher professional development and its impact on an education with quality under the protection of a society pronounced by advances in the technological field.